(untitled) (Journal of the College of Education for Women, 2019)
The research targets exploring the designs of the kindergartens’ libraries in Baghdad for the perspective of the teachers as well as possible methods of improvements, considering the importance of this type of furniture for the child and its vital role in getting the child into the habit of reading and browsing, since the kindergarten library is the first of its kind that the child encounters in his life, if the relationship between the child and the library is of a positive type the experience with both printed and non-printed materials will be joyful and this type of relationship continues and strengthen with all other types of libraries over time. To achieve the goals of the research, the researcher prepared a focused survey sheet that incorporates a set of questions designed for kindergarten teachers to first identify the current status of the libraries then to understand their perspective of the best methods to improve such libraries and make them more exciting and suitable for a kindergarten child. After validating the survey tool by a number of design experts and child psychology specialists, the survey has been distributed to the kindergarten teachers (research sample) of a total of (20) teacher that have been sampled from (5) public kindergartens distributed over both Karkh and Risafa boroughs of Baghdad. After collecting the survey data and using the percentage as statistical mean to calculate the results, the results showed that most of the kindergartens do not have a library for the kindergarten child and if they do these libraries and not designed to be suitable for this age and mostly designed in shapes and colors and sizes that are traditional for ages older than those of a kindergarten children ages, as for the teachers’ suggestions of what would be suitable designs for such libraries the all agreed that they need to be of sizes, shapes, colors, and internal partitions that are more suitable for a child and more capable of exciting and catching the attention of the child towards the library in addition to the ease of use by all children. The child towards the library in addition to the ease of use by all children.